Characterising coordination strategies during initial acceleration in sprinters ranging from highly trained to world class - Donaldson, B.; Bezodis, N.; Bayne, H. (Journal of Sports Sciences, 2023)
Identifying coordination strategies used by sprinters and features that differentiate these strategies will aid in understanding different technical approaches to initial sprint acceleration. Moreover, multiple effective coordination strategies may be available to athletes of similar ability, which typical group-based analyses may mask. This study aimed to identify sub-groups of sprinters based on thigh-thigh and shank-foot coordination during initial acceleration, and assess sprint performance across different combinations of coordination strategies. Angular kinematics were obtained from 21 sprinters, and coordination determined using vector coding methods, with step 1 and steps 2-4 separated for analysis. Performance was assessed using metrics derived from velocity-time profiles. Using hierarchical cluster analysis, three distinct coordination strategies were identified from thigh-thigh and shank-foot coordination in step 1 and two strategies in steps 2-4. Coordination strategies primarily differed around early flight thigh-thigh coordination and early stance shank-foot coordination in step 1, while timing of reversals in thigh rotation characterised differences in later steps. Higher performers tended to have greater lead thigh and foot dominance in step 1 and early swing thigh retraction in steps 2-4. The novel application of cluster analysis to coordination provides new insights into initial acceleration technique in sprinters, with potential considerations for training and performance.